Effect of Plant Growth Regulator-Flora on the Growth and Yield of Transplanted Aman Rice - Hossain, Nahid; Paul, Alok Kumar; Alam, Ishrat; Mollick, Md. Omar Ali; Miajee, Shah Jalal (International Journal of Bio-resource and Stress Management, 2020)
The experiment was conducted in the farm area of Sher-e-Bangla Agricultural University, Sher-e-Bangla Nagar, Dhaka during the period of July to November, 2015 to find out the effect of plant growth regulator-flora on the growth and yield of transplanted aman rice (BR 11-Mukta). The experiment comprised of 8 treatments as- T0: Control condition (No chemical fertilizer, no Flora), T1: Recommended Fertilizer Doses-RFD (120, 20, 80, 16 and 2 kg ha-1 of N, P, K, S and Zn, respectively), T2: RFD+1 time spray of Flora, T3: RFD+2 times spray of Flora, T4: ½ RFD+1 time spray of Flora, T5: ½ RFD+2 times spray of Flora, T6: No chemical fertilizer+1 time spray of Flora and T7: No chemical fertilizer+2 times spray of Flora. Data on different yield contributing characters, yield, and characteristics of post-harvest soil was recorded and significant variation was observed for different treatments. At harvest, the tallest plant (117.60 cm) was recorded from T3, while the shortest plant (88.85 cm) in T0 treatment. The highest number of filled grains panicle-1 (86.27) was recorded in T3, whereas the lowest number (68.53) in T0 treatment. The highest grain yield (5.13 t ha-1) was recorded in T3, while the lowest (2.78 t ha-1) in T0 treatment. The highest total nitrogen (0.632%) was recorded from T3, while the lowest (0.369%) in T0 treatment.